Ebola Survivor Corps: employing Ebola survivors as health educators and advocates in communities affected by Ebola in northern Sierra Leone - Nell Bond, PhD; Sallieu Sesay; Abdulai Kamara; Jenna Bates; Johana Teigen; Jeni Stowlow, MPH; Andrew Bennett, MSc; Sarah Paige, PhD; Lina Moses, PhD (Elsevier, 2019)
Background: The 2014-16 west African Ebola outbreak resulted in 28 652 cases and more than 11 000 deaths. Survivors were faced with persistent health sequelae, stigma, and loss of livelihood. Additionally, the outbreak shattered an already weak health-care system in Sierra Leone. Ebola Survivor Corps (ESC), was founded in 2015 to address Ebola survivor concerns and strengthen the capacity of the health sector in Sierra Leone. ESC employs Ebola survivors as survivor health advocates to provide health education, facilitate access to health care, and elevate their status to one of a trusted source of health information. Here, we describe a needs assessment to identify strengths and challenges of ESC and to inform its future direction. Methods: Koinadugu district in Sierra Leone was selected as the initial ESC programme site in response to needs identified through interviews with local stakeholders. Koinadugu is particularly difficult to reach by road, resulting in poor access to health care and low health literacy. In July, 2018, we undertook an evaluation and needs assessment of the ESC in Koinadugu. The evaluation of ESC was conducted by qualitative surveys and semi-structured interviews administered in the local language, either Krio or Kuranko. Participants were selected through convenience sampling or referred by survivor health advocates. The needs assessment to inform future programming was conducted using qualitative focus groups and health screenings. The evaluation and assessment were done in the communities of Kumala, Bandakoro, Kandaya, Farekoro, and Yoria. Findings: Data were collected from 45 community members for the programme evaluation and 34 Ebola survivors for the needs assessment in July, 2018. We found that ESC provides a needed service that the government is not able to supply for logistical reasons. Survivor health advocates are enthusiastic health educators and provide a richness of information through one-on-one meetings with community members. Additionally, survivor health advocates are viewed as respected sources of health information in their communities and they report reduced stigma. In 2018, survivor health advocates reached over 80 communities, with 23 295 individual contacts, providing education on locally relevant infectious and chronic disease topics. Interpretation: The work of the ESC remains relevant, especially because of the gaps in services after the closure of Koinadugu Ebola survivor programmes. Communication and transport remain challenging in this remote area. Initial programme goals have been met; however, our assessment revealed additional service and programme needs and together with the Ebola survivor community we have identified new directions for the programme. These include the development of health clubs to deepen knowledge of community-determined health topics and community initiative grants to improve livelihood security. Funding: Health: Dialogue, Creativity, Practice, Ltd.